Sources of excess steroid prescriptions and clinical adverse outcomes associated with steroid excess in patients with inflammatory bowel disease: The Leeds IBD Steroids study. Issue 3 (24th May 2022) - Rosiou, Konstantina; Carbonell, Jenelyn; Dolby, Vivien; Monfared, Niloufar; Raine, Tim; Selinger, Christian P.
Summary: Background: Corticosteroids remain important for managing inflammatory bowel disease (IBD) flares. Steroid excess, however, may be a marker of poor care. Patients access steroid prescriptions from primary (General Practitioners [GP]) or secondary care (hospital‐based). Sources of prescriptions and associated outcomes are not well described. Methods: Patients attending IBD clinics with linked primary care information were included. We examined appropriateness and timeliness of treatment escalation and avoidability of steroid excess in relation to prescription sources. Results: Of 2246 patients, 33% were exposed to steroids over 2 years. Primary care issued 28% of prescriptions. Secondary care prescriptions were more often of appropriate dose and duration (85% vs 41%, p < 0.001). Further flares occurred in 50% of patients prescribed steroids from primary care (vs 39%; p = 0.003). Steroid excess was observed in 15%. Patients with steroid excess who received prescriptions from primary care that were not communicated to secondary care less often received timely treatment escalation (49% vs 66%, p = 0.042) and steroid excess was more often avoidable (73% vs 56%, p = 0.022). Patients with steroid excess had higher risks of hospitalisation for IBD (OR = 12.33, 95% CI [8.89–17.11]), hospitalisation for infections (OR = 2.89, 95% CI [1.82–4.61]) and GP prescribed antibiotics (OR = 1.41, 95% CI [1.07–1.86]). Conclusion: Patients commonly access steroids through primary care, but doses and durations are frequently inappropriate with patients more likely to flare. Steroid excess was associated with IBD admissions, admissions for infections and antibiotic prescriptions. Improved liaison between primary and secondary care is required to reduce steroid excess. Abstract : This cohort study examined the source of steroid prescriptions for Inflammatory Bowel Disease in Leeds and consequences of steroid excess. Patients were more likely to flare after primary care prescriptions. Steroid excess was associated higher risks for hospital admission for IBD, hospital admissions for infections and need for antibiotics prescriptions in primary care.